English Teachers Views On Changes To The Independent Curriculum In English Language Learning - Fitri Waruwu (Jurnal Bima : Pusat Publikasi Ilmu Pendidikan Bahasa dan Sastra, 2024)
The aim of this research is to determine teachers' perceptions of curriculum changes independence in the context of learning methods regarding changes in the independence curriculum. On in this research, the method used is a qualitative descriptive research method and the data obtained is from the results of interviews. Teacher perceptions towards changes to the independent curriculum itself aims at teachers' perceptions of curriculum changes independence, namely how teachers understand the concept of an independent curriculum, analyzing the impact of the curriculum independence in teaching and learning as well as obstacles and challenges in implementing the curriculum independent. Where the curriculum is a very important and determining component in implementation of education. And functions as a tool for achieving educational goals, if the goal if education changes then automatically the curriculum must also be changed.